Prevalence of allergic rhinitis among elementary and middle school students in Changsha city and its impact on quality of life. Issue 11 (22nd September 2015) - Song, Y; Wang, M; Xie, J; Li, W; Zhang, X; Wang, T; Tan, G
Abstract: Objectives: To investigate the prevalence of allergic rhinitis among elementary and middle school students and examine its impact on their quality of life. Methods: Stratified sampling and cluster sampling surveys were performed among 10–17-year-old students in Changsha city from June 2011 to April 2012. Results: In the stratified sampling survey, the self-reported allergic rhinitis rate was 42.5 per cent. Further examination demonstrated that the average prevalence of allergic rhinitis was 19.4 per cent. The cluster sampling survey demonstrated that 214 of 814 students appeared to be atopic (26.3 per cent). The prevalence of allergic rhinitis and asthma was 17.2 and 2.1 per cent, respectively. In total, 71 atopic individuals (8.7 per cent) were without any symptoms of allergic disease. Further analysis showed that allergic rhinitis influenced the students' sleep, emotions and memory ( p < 0.001). Conclusion: The prevalence of allergic rhinitis was 15.8 –19.4 per cent, showing an increase with age. Allergic rhinitis affected students' sleep, emotions and memory.